Immunomodulatory R848-Loaded Anti-PD-L1-Conjugated Reduced Graphene Oxide Quantum Dots for Photothermal Immunotherapy of Glioblastoma - Yu-Jen Lu; Reesha Kakkadavath Vayalakkara; Banendu Sunder Dash; Shang-Hsiu Hu; Thejas Pandaraparambil Premji; Chun-Yuan Wu; Yang-Jin Shen; Jyh-Ping Chen (MDPI AG, 2024)
Glioblastoma multiforme (GBM) is the most severe form of brain cancer and presents unique challenges to developing novel treatments due to its immunosuppressive milieu where receptors like programmed death ligand 1 (PD-L1) are frequently elevated to prevent an effective anti-tumor immune response. To potentially shift the GBM environment from being immunosuppressive to immune-enhancing, we engineered a novel nanovehicle from reduced graphene oxide quantum dot (rGOQD), which are loaded with the immunomodulatory drug resiquimod (R848) and conjugated with an anti-PD-L1 antibody (aPD-L1). The immunomodulatory rGOQD/R8/aPDL1 nanoparticles can actively target the PD-L1 on the surface of ALTS1C1 murine glioblastoma cells and release R848 to enhance the T-cell-driven anti-tumor response. From in vitro experiments, the PD-L1-mediated intracellular uptake and the rGOQD-induced photothermal response after irradiation with near-infrared laser light led to the death of cancer cells and the release of damage-associated molecular patterns (DAMPs). The combinational effect of R848 and released DAMPs synergistically produces antigens to activate dendritic cells, which can prime T lymphocytes to infiltrate the tumor in vivo. As a result, T cells effectively target and attack the PD-L1-suppressed glioma cells and foster a robust photothermal therapy elicited anti-tumor immune response from a syngeneic mouse model of GBM with subcutaneously implanted ALTS1C1 cells.